Clonorchiasis in Patients with Biliary and Pancreatic Diseases: Diagnosis and Risk Factors. (24th February 2020) - Liao, Guolin; Ruan, Huaqiang; Peng, Peng; Liu, Shiquan; Qin, Jianfu; Liang, Zhihai; Tang, Guodu; Qin, Mengbin; Huang, Jie'an
Abstract : Background . Many epidemiological studies have investigated the risk factors for clonorchiasis, but endoscopic findings of this disease in endoscopic retrograde cholangiopancreatography (ERCP) have not been well characterized. In this study, we evaluated clonorchiasis in ERCP in patients with biliary and pancreatic diseases. Methods . This was a retrospective two-center study in hospitalized patients who received ERCP between January 2012 and October 2018. All patients were divided into clonorchiasis and nonclonorchiasis groups. Data were analyzed using univariate analysis and multivariate analyses. Results . A total of 1119 patients were included, and clonorchiasis was diagnosed in 19.2% patients. Detection of Clonorchis sinensis eggs in bile samples was higher than that in fecal samples (85.9% vs. 58.7%; P = 0.001 ). In multivariate analysis, male patients (95% confidence interval (CI): 1.945–4.249, P = 0.0001 ), age ≤ 60 years old (95% CI: 1.212–2.474, P = 0.003 ), patients with papilla fistula (95% CI: 0.081–0.900, P = 0.033 ), and patients with a common bile duct (CBD) diameter < 12  mm (95% CI: 1.093–2.130, P = 0.013 ) were associated with clonorchiasis incidence. Nonclonorchiasis endoscopic diagnosis did not significantly correlate with clonorchiasis incidence (P > 0.05 ). Conclusions . The detection of C. sinensis eggs was significantly higher in bile than in fecal samples; thus, bile samples represent a preferable sample for the diagnosis of clonorchiasis in patients with biliary obstruction. We found that male, age ≤ 60 years old, and CBD diameter < 12  mm were independent risk factors for clonorchiasis, while papilla fistula was a protective factor.